Strategi Pengembangan Koleksi Pada Perpustakaan Desa Dan Taman Bacaan Masyarakat Di Era Kenormalan Baru - Yunus Winoto (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2020)
This study examines the strategy of developing collections in village libraries and community reading parks entering a new era of normalcy. The location of this research was conducted in several village libraries and community reading parks in West Bandung Regency. The method used in this study uses literature review. Understanding literature review is a research methodology that aims to collect and extract the essence of previous research and analyze some of the experts' overview written in the text. the type of review literature used in this paper is the semi-systematic type or also called the narrative review approach. The choice of semi-systematic approach in this paper because this paper will describe a fairly complex topic in this research that is about collection development starting from the understanding of collection development, collection development stages, needs analysis, concept of selection, procurement, to evaluation of development collection . From the results of the study it can be stated that the process of developing collections that have been running must begin to be improved in line with the adaptation of new habits, the type of collection must have begun to shift to digital collections and online-based services using social media must have begun to be applied. Collection about health, especially about clean and healthy lifestyle, health protocols and reading about the corona virus is an absolute collection that must be in the village library and community reading park